Relación entre la satisfacción laboral y motivación laboral en trabajadores - Olcese Caballero, Natalie Milagros (2024)
Organizational success depends on the workforce and its ability to achieve established objectives. To achieve this, it is essential that employees are satisfied with their work. Work motivation is one of the variables that is most related to job satisfaction, since the employee's ability to achieve an optimal level of job satisfaction depends on the extrinsic and intrinsic motivational factors. The objective of the present applied review was to identify the relationship between job satisfaction and work motivation in workers. Four databases were used, identifying inclusion and exclusion criteria, from which 10 articles were selected. The results reveal significant correlations between satisfaction and work motivation. The discussion is carried out based on the main and secondary findings, where, through multivariate analysis, a relationship was found with turnover intention and the leadership style used. Additionally, relevant interventions in the field of psychology are shared. It is concluded that there is a positive compensation between job satisfaction and work motivation.